On the Effects of Income Heterogeneity in Monopolistically Competitive Markets - Sergei Kichko; Pierre M. Picard; Pierre Picard (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper studies the market and welfare effects of income heterogeneity in monopolistically competitive product markets in the context of nonhomothetic preferences. In a closed economy, where richer individuals' expenditures are less sensitive to price change compared to poorer ones', a mean-preserving contraction of income distribution entices firms to charge higher markups, reduce output, and fosters creation of new varieties. General equilibrium effects have a negative impact on poorer individuals and, in specific circumstances, on the whole population. In an open economy with free trade, lower income inequality in one country creates price divergence between trading countries. Lower inequality not only further decreases trade volumes and values but also creates a general equilibrium effect that may negatively affect poor individuals. Finally, general equilibrium effects are shown to be quantitatively nonnegligible.
Keywords: D43; L16; F12; 330; monopolistic competition; nonhomothetic additive preferences; income inequality; pricing-to-markets; welfare; trade